SELF-EFFICACY, RELIGIOSITY, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN POLICE HUMAN RESOURCES BUREAU - Maris , Septi; Wahyu Utomo , Kabul; Wihadanto , Ake (Catholic University Musi Charitas, 2024)
The police are part of the government. Therefore, in the context of bureaucratic forms in the police environment, efforts to organize and improve the welfare of police officers are very fundamental considering that they are closely related to the mission of changing police culture. necessary needs. Power (reform of the cultural sphere). It is hoped that the new salary system will provide maximum prevention against material temptation and seduction (collusion) from all members of the National Police. But in reality there is. This research uses variance-based Structural Equation Modeling (SEM) techniques or better known as SEM PLS (Partial Least Square) and is assisted by SMART PLS 2.0.M3 software. 6. Self efficacy, organizational commitment to organizational citizenship behavior: Path coefficient = 3.609 > T-Table = 1.982, meaning that the moderator variable (organizational commitment) moderates the influence of an endogenous variable (self efficacy) on the exogenous variable (Organizational citizenship behavior). Religiosity, Organizational Commitment to Organizational Citizenship Behavior: Path coefficient = 1.887 > T-Table = 1.982, meaning that the moderator variable (Organizational Commitment) moderates the influence of an endogenous variable (Religiosity) on the exogenous variable (Organizational Citizenship Behavior).